The Kinship of Theory and Practice in Aristotle - Edwards, Alexander (Université d'Ottawa / University of Ottawa, 2024)
Short Form: The fragments of Aristotle's Protreptic are internally consistent under dialogical interpretation, if one accepts my thesis about the 'three-ring circus of ambiguity' in their usage of sophia and phronêsis. Thus interpreted, the content of the Protr. is compatible with the content of his 'mature' ethical and political treatises, particularly the Nicomachean Ethics and Politics, though they differ in emphasis, due to their rhetorical context. Their compatibility is to be determined primarily in terms of their solution to the dilemma of 'quietist' and 'activist' accounts of eudaimonia. The primary division of his ethical and political works is analogous to and, moreover, rooted in that of his psychology. Both are analogous to and, moreover, 'serially' related to his account of the divine life in the twofold sense of "prime mover". Thus, his accounts of life, the good life, and the divine life are not only analogous but also systematically connected. -- Long Form: This dissertation investigates the contrast and identification of theory and practice in Aristotle. It comprises three chapters. The first "reweaves" the lost Protreptic of Aristotle, demonstrating the internal consistency of the fragments under dialogical interpretation. If one accepts my thesis concerning the '3-ring circus of ambiguity' in the fragments as regards their usage of sophia and phronêsis, wherein each of the three characters ('Isocrates', 'Heraclides' and 'Aristotle') uses these terms in their own way in light of their ('quietist' or 'activist') account of eudaimonia, I contend, the fragments of the Protreptic are internally consistent and, moreover, consistent with the account of eudaimonia in 'mature' treatises such as the NE and Pol.: dialogically interpreted, the fragments of the Protr. are consistent with the NE and Pol. (contra Jaeger et al.). But that claim depends on my reading of these treatises in respect of the dilemma of 'quietism or activism?', which dramatically structured the Protreptic (as I show in Part 1). Hence, Part 2 articulates my reading of the relevant arguments in these treatises. I argue that they are consistent with, though differ in emphasis from, the fragments of the Protr. That difference in emphasis, I contend, is due to 'rhetorical context', not only in the sense that the work was addressed to an 'exoteric' (vs. 'esoteric') audience, but in the sense of the 'circus of ambiguity' at work in the fragments, which develops as the conversation progresses and culminates in the ultimate conclusion of 'Aristotle'. The conclusion of Part 2 considers (what I argue is) the physical and metaphysical analogue of the ethical and political dilemma: the activity of sophoi and phronimoi is akin to that of 'the God and the total cosmos' (motionless activity and changeless motion). Having shown that his accounts of the good life and of the divine life are analogous, I turn in chapter 3 to (what I argue) is their analogue in his psychology, the 'basic' division of De Anima between critical and kinetic functions of the soul, which I argue 'develops' or 'transforms' into that of theoretical and practical nous and thus of sophia and phronêsis in the ethical and political works. Thus, I connect his accounts of life, the good life, and the divine life not only analogically but 'serially', argue that the question of the systematicity of the corpus reduces to the question of its seriality, and conclude with my account of how these serial 'transformations' operate not only in his treatment of, e.g., soul and body, but also in the relationship between treatises or of the treatises to themselves, arguing for their 'serial' unity.